2016
DOI: 10.1364/josab.33.000189
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-on-sapphire mid-IR wavefront engineering by using subwavelength grating metasurfaces

Abstract: Subwavelength high-contrast gratings (sub-λ HCGs) were pursued to design mid-IR optical devices based on wavefront engineering. Unlike metallic counterparts, dielectric and semiconductors offer low-loss operation over a wide spectral range. Silicon gratings on sapphire substrate are proposed here as the device platform due to their transparency at near-IR to mid-IR wavelengths. The proposed generic methodology manipulates the wavefront of the reflected wave based on the phase and magnitude of reflectivity for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…To increase robustness, the under-cladding can instead be replaced by a more transparent material, such as sapphire (transparent out to ∼4.5 µm). Siliconon-sapphire is commercially available and has been extensively studied [39][40][41][42][43][44][45][46][47]; however, it is a hard material that is difficult to etch, leading to scattering losses. Additionally, Chen et al have recently demonstrated a platform based on silicon on calcium fluoride (CaF 2 ), which extends the transparency window even further [48].…”
Section: Introductionmentioning
confidence: 99%
“…To increase robustness, the under-cladding can instead be replaced by a more transparent material, such as sapphire (transparent out to ∼4.5 µm). Siliconon-sapphire is commercially available and has been extensively studied [39][40][41][42][43][44][45][46][47]; however, it is a hard material that is difficult to etch, leading to scattering losses. Additionally, Chen et al have recently demonstrated a platform based on silicon on calcium fluoride (CaF 2 ), which extends the transparency window even further [48].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, using the proposed method results in a short circuit current which is 2.97 times higher than a simple solar cell using the same amount of crystalline silicon. The short circuit current enhancement achieved in this work is much higher than the values reported in previous works [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. To study the effect of the incident angle, Figure 12 illustrates the short circuit current enhancement for different angles of incidence.…”
Section: Using Dielectric Sierpinski Nano-carpet In the Solar Cellmentioning
confidence: 60%
“…Furthermore, since the structure is completely symmetric, it provides exactly the same response for TE and TM polarisations of the incident light. The consistency of the absorption for TM and TE polarisations is one of the important advantages of the proposed solar cell when compared with previous works [12, 13, 20].…”
Section: Solar Cell With Metallic Sierpinski Nano‐carpetmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, suitable designs for terahertz and lower frequencies can also benefit from engineered metamaterials with ultrahigh index of refraction [42]- [44]. Mid-IR wavefront shaping can be carried out also using all-dielectric subwavelength highindex-contrast gratings offering a low-loss performance [45]. Finally, compact multifocal nanolenses might be developed following for instance the procedure of Refs.…”
Section: Discussionmentioning
confidence: 99%